Agriculture on the Move: Exploring Regional Differences in Farm Exit Rates - Thomas Glauben; Hendrik Tietje; Christoph R. Weiss (Kiel University, Department of Food Economics and Consumption Studies, 2003)
This paper investigates the relationship between farm exits and various farm, family, and regional characteristics during the period of 1991 to 1999. Using county-level data for 326 regions in western Germany, econometric cross section estimations indicate that exits from farming are strongly influenced by farm and family characteristics. In particular, exit rates are higher in regions with smaller farms. Further, farm exits are closely related to retirement and succession considerations. Exit rates are lower in regions with a high share of part-time farms, which indicates that off-farm income has a stabilizing impact on structural change in agriculture.
Keywords: 330; Farm exit; county-level census data; cross-section estimation; Germany; Landwirtschaft; Marktaustritt; Liquidation; Familiensoziologie; Region; Nebenerwerbslandwirtschaft; Schätzung; Deutschland